Does culture influence holistic and analytic processing styles existing in the east and west? - Lum, Alycia We Ying. (2012)
This paper reviews recent cross-cultural evidences of holistic and analytic processing styles existing between East Asians and Westerners. Contrasting orientations present in low-order cognitive processes such as attentional patterns and higher order processes such as perceptual categorization and logical reasoning are considered. Findings from previous literature that East Asians tend to have broader attentional breadths, base categorizations on thematic relationships and rely on intuition, while Western individuals tend to have narrow attentional focus, make rule-based categorizations and rely on formal logic, is evaluated. In addition, this review considers the two cultural factors of self-construal and schooling in contributing to these cognitive differences. Evaluations support the notion that cognitive differences are a reflection of different cultural demands and social practices present in both cultures, which moulds contrasting preferences for holistic or analytic styles of processing. Implications and directions for future cross-cultural research in this area are suggested and the effects of increasing multiculturalism on cognition are addressed.